Competence, achievement goals, motivational climate, and pleasant psychobiosocial states in youth sport - Bortoli, L.; Bertollo, M.; Comani, S.; Robazza, C. (Journal of Sports Sciences, 2011)
We examined the three-way interactions among competence (actual and perceived), individuals' dispositional goal orientation (task/ego), and perceived sport motivational climate (mastery/performance) in the prediction of pleasant psychobiosocial states (i.e. emotion, cognition, motivation, bodily reaction, movement, performance, and communication) as conceptualized by the Individual Zones of Optimal Functioning model. The sample consisted of 320 Italian youths (160 girls and 160 boys) aged 13-14 years who were involved in individual or team sports. The assessment included a perceived competence scale, a goal orientation questionnaire, a motivational climate inventory, and pleasant psychobiosocial descriptors. An actual competence scale was also administered to coaches asking them to assess their youngsters. Moderated hierarchical regression analysis showed that perceived competence, actual competence, and task orientation were the strongest predictors of pleasant psychobiosocial states. Moreover, actual competence and perceived competence interacted in different ways with dispositional goal orientations and motivational climate perceptions in the prediction of psychobiosocial states. It is therefore recommended that both constructs be included in motivational research.